Avaliação de risco em máquinas – os benefícios do método HRN (Hazard Rating Number) - Silva, Isabel Barreto Rochedo (Universidade do Vale do Rio dos Sinos, 2011)
Because of the high number of accidents at work in Brazil is essential the knowledge of hazards and risks in the processes and also in the machinery and equipment manufacturing facilities. Therefore, has the legal support and inspections standards (norms) on NR 12- Safety at work in machinery and equipment and ABNT NBR 14009 - Safety of machinery:Principles for risk assessment, which require the risk assessment in any stage, since the beggining of projects until the adequacy of security machines. The article presents how a risk assessment should be performed and in parallel shows three distinct methods of assessment, the method of the Matrix, Graph and HRN (Harzard Rating Number). In the end, exemplifies the use of methods and apply them in two machines, a hydraulic press and a hydraulic injector. Thus explaining the positive and negative characteristics of all these methods, ending with the greatest benefits of the risk assessment method HRN.
Keywords: Avaliação de risco; Máquinas; Métodos de avaliação; Risk assessment; Machine; Assessment methods